Landscape context shifts the balance of costs and benefits from wildflower borders on multiple ecosystem services. Issue 1884 (1st August 2018) - Grab, Heather; Poveda, Katja; Danforth, Bryan; Loeb, Greg
Abstract : In the face of global biodiversity declines driven by agricultural intensification, local diversification practices are broadly promoted to support farmland biodiversity and multiple ecosystem services. The creation of flower-rich habitats on farmland has been subsidized in both the USA and EU to support biodiversity and promote delivery of ecosystem services. Yet, theory suggests that the landscape context in which local diversification strategies are implemented will influence their success. However, few studies have empirically evaluated this theory or assessed the ability to support multiple ecosystem services simultaneously. Here, we evaluate the impact of creating flower-rich habitats in field margins on pollination, pest control, and crop yield over 3 years using a paired design across a landscape gradient. We find general positive effects of natural habitat cover on fruit weight and that flowering borders increase yields by promoting bee visitation to adjacent crops only in landscapes with intermediate natural habitat cover. Flowering borders had little impact on biological control regardless of landscape context. Thus, knowledge of landscape context can be used to target wildflower border placement in areas where they will have the greatest likelihood for success and least potential for increasing pest populations or yield loss in nearby crops.